Indigena Jibaro - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observó el rostro de un indigena Jibaro conocido tambien como mayoruna atacado por el mal de la uta.
ENGLISH: The face of a Jibaro indigenous person, also known as mayoruna, attacked by the uta disease was observed.

SPANISH: Se observó el rostro de un indigena Jibaro conocido tambien como mayoruna atacado por el mal de la uta.
ENGLISH: The face of a Jibaro indigenous person, also known as mayoruna, attacked by the uta disease was observed.
Jibaro indigenous person
Keywords: Iquitos (Perú)|~|Native Communities|~|Perú|~|Indigenous or Native populations|~|Amazonian Faces|~|Iquitos (Perú)|~|Comunidades Nativas|~|Perú|~|Poblaciones Indigenas u Originarias|~|Rostros Amazonicos|~|Iquitos (Peru)|~|Native Communities|~|Peru|~|Indigenous or Native Populations|~|Amazonian Faces